AMS 14C Dating at the Scottish Universities Environmental Research Centre (SUERC) Radiocarbon Dating Laboratory. Issue 1 (11th January 2016) - Dunbar, E; Cook, G T; Naysmith, P; Tripney, B G; Xu, S
Abstract: This paper describes all the major procedures adopted by the Scottish Universities Environmental Research Centre (SUERC) Radiocarbon Dating Laboratory. This includes sample pretreatment, graphite production, accelerator mass spectrometry (AMS) measurement, associated stable isotope measurements, data handling, and age calculations, but with the main emphasis being on the chemical pretreatment methods. All of the above enable the laboratory to provide a complete analytical service comprising advice on sample selection, preparation and analysis of samples, and Bayesian analysis of resulting 14 C (and other) data. This applies to both our research and commercial activities. The pretreatment methods that we mainly focus on are used to remove contaminant carbon from a range of sample types or to isolate a particular chemical fraction from a sample prior to combustion/hydrolysis, graphitization, and subsequent AMS 14 C measurement. The methods described are for bone (collagen extraction, with and without ultrafiltration), cremated bone, tooth enamel, charcoal, grain, carbon residues, shell, wood (including alpha-cellulose isolation), peat, sediments, textiles, fuel/biofuel, and forensic samples.